Pengaruh Persepsi Sikap, Norma Subjektif dan Persepsi Kontrol Perilaku terhadap Kepatuhan Wajib Pajak Orang Pribadi - Karolina, Monika; Noviari, Naniek (E-Jurnal Akuntansi, 2019)
The purpose of this research was to determine effect of variabels in theory of planned  behavior namely perception ofattitude, subjective norm and behavioral control of individual  taxpayer compliance. This research was conducted in East Denpasar Primary Tax Office  with 100 individual taxpayes registered as a samples and using non probability of sampling  method, especially accidental sampling. The data was collected through the distribution of  the questionnaire. Analysis techniques that is used is multiple linear regression. Based on  the results of the analysis it was found that the perception of the attitude, subjective norms,  and perceptions ofcontrol behavior had a positively influence individual taxpayer. Keywords:  Compliance taxpayers, theory of planned behavior, attitude, subjective norm,  perception of control behavior.